Pulse oximetry screening for critical cardiovascular malformations in infancy. (29th September 2015) - Prudhoe, S; Abu-Harb, M; Richmond, S; Wren, C
Abstract : Introduction: Babies with cardiovascular malformations are often asymptomatic at birth and many fail to be detected by the newborn examination. Pulse oximetry screening has been advocated to improve detection of cardiovascular malformations in newborns. Aims: To investigate the contribution of postductal pulse oximetry screening to early diagnosis of critical cardiovascular malformations. Methods: A retrospective study in a large district general hospital from 1st May 1999 to 30th April 2009. All babies underwent routine oxygen saturation measurement in one foot prior to discharge. Babies with oxygen saturations <95% were examined by a midwife. If examination was abnormal or saturation was persistently below 95% an echocardiogram was performed. All babies diagnosed with cardiovascular malformations born during the study period were identified from a database maintained within the hospital. Critical cardiovascular malformations were defined as those in infants with hypoplastic left heart, pulmonary atresia with intact septum or with ventricular septal defect, transposition of the great arteries, interruption of the aortic arch, coarctation of the aorta, aortic stenosis, or total anomalous pulmonary venous connections who died or required intervention before 12 months of age. Significant malformations were defined as all other diagnoses of structural heart disease (excluding PDA) requiring intervention or causing death in the first year. Results: Cardiovascular malformations were identified in 321 of 32 120 live births (10 per 1000). 38 (11%) infants had critical malformations, of which 12 (32%) were detected prenatally, 1 (3%) became symptomatic prior to saturation screening, 6 (16%) were detected by routine newborn examination, 9 (24%) were detected solely by pulse oximetry and 10 (25%) were discharged without diagnosis. Of 10 babies discharged prior to diagnosis one had an interrupted aortic arch, four had coarctation, two had pulmonary atresia with VSD, two had total anomalous pulmonary venous connections and one had transposition. 37 (11%) infants had significant malformations, one of which was first detected by pulse oximetry. Conclusions: Routine pulse oximetry in conjunction with newborn examination may improve detection of some cardiovascular malformations. However, 25% of babies with critical malformations are discharged undiagnosed. Pulse oximetry screening cannot exclude the presence of a cardiovascular malformation.